The Effectiveness of the Discovery Learning Model on the Ability to Identify Life Values in the Short Stories of Phase F XI High School Students - Guci, Aqlina Ulya; Helda, Trisna; Yulianti DN, Upit (Pelangi (e-Journal), 2024)
This research was motivated by knowing the effectiveness of the Discovery Learning model on the ability to identify life values in Phase F XI high school students' short stories. Research purposes . First, describe the ability to identify life values in Phase F XI students' short stories before using the Discovery Learning learning model. Second, to describe the ability to identify life values in Phase F XI high school students' short stories after using the Discovery Learning learning model. Third, describe the effectiveness of using the Discovery Learning learning model on the ability to identify life values in Phase F XI high school students' short stories. Type of experimental quantitative research. The research population was students of Phase F This research data is in the form of test scores for the ability to identify life values in short stories before and after using the Discovery Learning learning model through objective tests. Based on the results of the research, it was concluded that there was effectiveness in using the Discovery Learning model on the ability to identify life values in the short stories of Stage F XI students at SMA Negeri 7 Padang before and after using the Discovery Learning model.